2018
DOI: 10.1212/wnl.0000000000004794
|View full text |Cite
|
Sign up to set email alerts
|

Education Research: Difficult conversations in neurology

Abstract: Objective To characterize features of medical student exposure to difficult conversations during a neurology core clerkship. MethodsThis was a cross-sectional concurrent nested mixed methods study, and all students rotating through a required neurology clerkship between 2014 and 2015 were enrolled. Data collection included an electronic communication tracker, baseline and end-of-clerkship surveys, and 4 facilitated focus groups. Students were asked to log exposure to patient-clinician conversations about (1) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 7 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…Consequently, health professionals have a responsibility to train in communications skills [77] and specifically in engaging in difficult conversations [85]. Evidence suggests that people with MS prefer an active role in decision-making [86,87], therefore health professionals must work towards empowerment through partnerships.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Consequently, health professionals have a responsibility to train in communications skills [77] and specifically in engaging in difficult conversations [85]. Evidence suggests that people with MS prefer an active role in decision-making [86,87], therefore health professionals must work towards empowerment through partnerships.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…5 In neurology clerkships, medical students frequently observe and participate in challenging conversations with patients. 4 In a prior study, we found that these encounters are valuable educational opportunities for students to gain real-time experience in communication skills, and that the difficult nature of these conversations presents both barriers to, and unique opportunities for, communication skills instruction. 4 This study was performed to understand the medical student perspective of participating in and observing challenging conversations, in order to inform future curricular design.…”
Section: Discussionmentioning
confidence: 97%
“…Many students will have their first real-life experiences with difficult conversations during their clinical rotations. Over half of medical students report directly participating in a difficult conversation during their clinical year 3,4 and as many as 29% of residents first delivered bad news to a patient during medical school. 5 In neurology clerkships, medical students frequently observe and participate in challenging conversations with patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly true in neurology, where the majority of students witness at least one difficult conversation about new disability or prognosis during their clerkship and residents participate in such conversations regularly. 36 Multiple studies have demonstrated role modeling to be among the most appreciated traits in highly respected clinical teachers, 16,19 though this is not uniformly the case. 29 Excellent clinical teachers consider this responsibility important and make conscious choices about which traits to model and how.…”
Section: Practical Advantagesmentioning
confidence: 99%